Pharmaceutical Public Health: A Mixed-Methods Study Exploring Pharmacy Professionals’ Advanced Roles in Public Health, Including the Barriers and Enablers - Diane Ashiru-Oredope; Roeann Osman; Adeola H. Ayeni; Eleanor J. Harvey; Maria Nasim; Emma Wright; Christina Narh; Uju Okereke; Tasmin Harrison; Christopher Garland; Cecilia Pyper; Andrew Evans; et al. (Pharmacy)
Background: In the UK and globally, pharmacy professionals (pharmacists and pharmacy technicians) contribute to the delivery of local and national public or population health interventions. The existing literature on pharmaceutical public health predominantly focuses on micro-level activities, primarily describing community pharmacies delivering public health interventions to individuals. There is little-known evidence on pharmacy professionals’ involvement in delivering public health interventions at meso- (e.g., organisational) and macro (national/policy) levels, nor to what extent pharmacy professionals have specialist/advanced roles within public health practice. This study specifically explored pharmacy professionals’ specialist/advanced roles within public health as well as the opportunities and barriers to career development. The analyses of this mixed-methods study makes a series of important recommendations for future action. Methods: This study included two independent cross-sectional electronic surveys for pharmacy professionals and public health professionals, a call for evidence, and two workshops to develop recommendations. Results: Pharmacy professionals (n = 128) and public health professionals (n = 54) across the UK participated in the surveys. Most of the Pharmacy Professionals respondents were female (70%), pharmacists (85%), working in primary (33%) or secondary (25%) care settings, mainly based in England (75%), and most (63%) lacked formal public health qualifications although they were involved in a diverse range of public health interventions. The public health professionals were mostly females (67%), practicing in England (58%). Both professional groups identified opportunities and barriers to pharmacy professionals’ involvement in public health. Almost half of the public health professionals respondents (44%) stated that they had a pharmacy professional working as part of their current public health teams. Eighty-seven percent of public health professional respondents (45/52) agreed that having pharmacists or pharmacy technicians specialising in public health would be beneficial or very beneficial. Most of the documents, reports, and case histories provided through the call for evidence were unpublished. The workshops generated 94 recommendation statements, highlighting collaboration and the need to acknowledge pharmacy professionals’ contributions to public health. Conclusion: The recommendations for strategic action at meso- and macro-levels included three main themes: adopting a national strategic approach to pharmaceutical public health, including improving commissioning; formalising pharmaceutical public health workforce development; and promoting further evidence-based pharmaceutical public health research and development.